2020
DOI: 10.1186/s13019-020-01091-5
|View full text |Cite
|
Sign up to set email alerts
|

Concurrence of primary pulmonary malignant melanoma with invasive pulmonary adenocarcinoma: a case report

Abstract: Background: Primary pulmonary malignant melanoma (PPMM) is an extreme rarity in clinic practice, accounting for only 0.01% of all primary pulmonary tumors. And its diagnosis should meet clinical and pathological diagnosis criteria in addition to excluding the possibility of metastatic melanoma. The mainstay of treatment is surgery. The concurrence of primary pulmonary malignant melanoma and invasive pulmonary adenocarcinoma has not been reported before. Case presentation: Herein we report the case of a 39-year… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 27 publications
(34 reference statements)
0
3
0
Order By: Relevance
“…Although meningiomas are commonly associated with the cranial meninges, the occurrence of these tumors in ectopic locations presents unique diagnostic, pathological, and therapeutic challenges. Since the first reported case in 1982, approximately 70 cases have been described in the literature [4–6]. PPM has a distinct predilection for occurrence in elderly women, with this demographic group presenting a higher incidence [7].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although meningiomas are commonly associated with the cranial meninges, the occurrence of these tumors in ectopic locations presents unique diagnostic, pathological, and therapeutic challenges. Since the first reported case in 1982, approximately 70 cases have been described in the literature [4–6]. PPM has a distinct predilection for occurrence in elderly women, with this demographic group presenting a higher incidence [7].…”
Section: Discussionmentioning
confidence: 99%
“…Notably, maximum standardized uptake value (SUVmax) alone cannot reliably distinguish between benign and malignant PPMs. Even PPMs with mild fluorodeoxyglucose uptake can be benign, whereas those with low SUVmax values may be malignant [6]. Moreover, distinguishing PPM from other pulmonary neoplasms and metastatic meningiomas can be complicated and necessitates a comprehensive diagnostic approach.…”
Section: Discussionmentioning
confidence: 99%
“…Summarizing the literature (1,3,4,7,(11)(12)(13)(14)(15) on lung melanin in recent years, we found that: (I) Pulmonary melanoma has no specific clinical manifestations, but it is frequently characterized by coughing, hemoptysis, dull chest pain, and other symptoms. (II) It is more likely to occur in the lower lobe of the left lung, the metastasis rate of mediastinal lymph nodes is lower than that of lung cancer, and the mutation rate of BRAF is low, but the prognosis is poor, and the median survival is 24.3 months.…”
mentioning
confidence: 89%